Core-Shell Structure of a Silicon Nanorod/Carbon Nanotube Field Emission Cathode. (1st November 2011) - Huang, Bohr-Ran; Yang, Ying-Kan; Lin, Tzu-Ching; Yang, Wen-Luh
Abstract : A novel core-shell structure of silicon nanorods/carbon nanotubes (SiNRs/CNTs) is developed for use in field emission cathodes. The CNTs were synthesized on SiNRs, using the Ag-assisted electroless etching technique to form the SiNRs/CNT core-shell structure. This resulting SiNRs/CNT field emission cathode demonstrated improved field emission properties including a lower turn-on electric field E on (1.3 V/μm, 1 μA/cm 2 ), a lower threshold electric field E th (1.8 V/μm, 1 mA/cm 2 ), and a higher enhancement factor β (2347). These superior properties indicate that this core-shell structure of SiNRs/CNTs has good potential in field emission cathode applications.